Digit amputation in small ruminants. (2nd March 2022) - Crilly, James Patrick; Reilly, Beth; Scott, Phil
Abstract : Digit amputation is an appropriate surgical response to septic pedal arthritis and other infectious problems of the deep digital tissues that will not respond to medical therapy. It may be performed under local, regional or general anaesthesia. The preferred approach is transection of distal P1. The recovery period is 3–4 weeks, and animals may be retained in the flock or herd for several years post surgery.